Pengaruh Electronic Word Of Mouth Dan Citra Merek Terhadap Keputusan Pembelian Eiger Di Indonesia - Tri Noverdo; Roslina; Nuzul Inas Nabila (CV. Multi Kreasi Media, 2023)
The rapid development of technology and the increasing level of competition for outdoor products in Indonesia, makes outdoor product businesses need to pay attention to positive E-WOM and a good image in the eyes of potential consumers, in order to make purchasing decisions for these outdoor products. One of the outdoor companies in Indonesia is the Eiger company. The purpose of this study was to examine the effect of electronic word of mouth and brand image variables as independent variables on purchasing decisions as the dependent variable on the Eiger brand in Indonesia. This study used a survey method by distributing questionnaires to 100 respondents. The sample used purposive sampling, namely a technique for determining the sample according to the criteria determined by the researcher. The analytical methods used in this study were validity test, reliability test, analysis phase using multiple linear regression, and hypothesis testing, namely the t test and F test and the coefficient of determination (R2 ), using the IBM SPSS 26 for windows application program. The results of this study indicate that electronic word of mouth and brand image variables have a significant effect on purchasing decision variables.